Benelli Bikes Purchase Decision in Makassar City - Mujahid; Nasyirah Nurdin; Syamsul Riyadi; Muh. Rial Ashar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Purchasing decision is a thought where individuals evaluate various options and decide on a choice on a product from many choices. Purchasing decisions are the stage in the purchasing decision-making process where consumers actually buy. The purpose of this study is to find out how the form of consumer decision making in choosing Benelli brand motorcycles in the city of Makassar. This type of research is a qualitative analysis, the results of the discussion found that consumers decide to buy Benelli brand motorcycles because they have a sense of satisfaction, quality and comfort when in Indonesia.